Biometric Identification: Face Recognition based on Iris Detection - Mohd Rizon, Mohd Juhari, Prof. Madya Dr. (International Exhibition of Inventions, 2010)
Prof. Madya Dr. Mohd Rizon and his team won silver at International Exhibition of Inventions of Geneva 2006, 5th - 9th April 2006 was held at Palexpo, Geneva, Switzerland.